Effectiveness of mobile health in symptom management of prostate cancer patients: a systematic review and meta-analysis - Hai Shan Chen; Hua He; Hai Hang Lin; Yuan Zhang; Nu Li; Ya Mei Li (Frontiers in Digital Health)
BackgroundMobile health (mHealth) is an accessible strategy to deliver health information and is becoming increasingly popular as a form of follow-up among medical staff. However, the effects of mobile health on the physical and mental health outcomes of patients with prostate cancer after discharge from the hospital remain unclear. This meta-analysis evaluated the current evidence regarding the effects of mHealth interventions on the outcomes of patients with prostate cancer.MethodsFour databases (PubMed, Cochrane Central electronic database, EMBASE, and Web of Science) were searched from inception to 8 November 2024 for randomized controlled trials (RCTs) comparing the effects of mobile health vs. usual care on the outcomes of patients with prostate cancer. Pooled outcome measures were determined using random effects models.ResultsIn total, 11 RCTs, including 1,368 patients, met the criteria for inclusion in this meta-analysis. The meta-analysis revealed a significant effect of mHealth interventions on long-term bowel function outcomes (standard mean difference = 0.19, 95% confidence interval = 0.01–0.37, P = 0.04, I2 = 0.00%) compared with the usual standard care or no mHealth. However, no significant differences were observed in the following outcomes: short-term and long-term effects on anxiety, depression, self-efficacy, psychological distress, and urinary and hormonal function, and short-term effects on bowel function.ConclusionsmHealth interventions can significantly improve long-term bowel function outcomes. However, more research is needed to confirm other physical and mental health outcomes.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, PROSPERO (CRD420250651320).